A Metaverse Where Users, NPCs and AI Agents Can Coexist - Markopoulos, Panagiotis; Smed, Jouni (United States, 2026)
The Metaverse is a rapidly evolving virtual ecosystem that offers endless possibilities for enhancing user experiences, encouraging interactivity, and allowing the exploration of immersive digital environments. This paper examines the critical role of NPCs (non-player characters) and AI agents in achieving these goals, emphasizing their ability to simulate lifelike behaviours and interactions that enrich the Metaverse. By drawing on recent advancements, such as the integration of AI bots on platforms like Facebook and Instagram, the paper explores how these agents can provide appropriate user support, entertainment, and companionship, while also enhancing the believability and vibrancy of virtual spaces.The paper also highlights a significant challenge. The overpopulation of user-created bots. Much like the rise of automated accounts on traditional social media platforms, an uncontrolled influx of these bots in the Metaverse could disrupt user social dynamics, dilute authentic interactions, and overcrowd the virtual environments. The resulting imbalance threatens to undermine the Metaverse's potential to deliver meaningful and enjoyable experiences. By researching and analysing the coexistence of NPCs, AI agents, users, and regulated bots, this paper promotes the idea of a Metaverse that supports artificial and human interactions, ensuring a dynamic, engaging, and sociable virtual environment for all participants.
Human-Computer Interaction & Emerging Technologies : Proceedings of the 16th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Orlando, Florida, USA 26-30 July 2025